Sustainability of concrete pavements considering traffic and de-icing agents - Rolf Breitenbücher; Robin Przondziono (Acta Polytechnica CTU Proceedings)
In concrete pavements, special conditions, that increase the likeliness of damaging reactions, as for example an alkali-silica reaction (ASR), prevail. Especially to the superposition of microstructural degradation caused by cyclic loading with an external alkali supply can influence the sustainability negatively. Concrete pavements are subjected to cyclic loadings by traffic and climate changes. These cause microcracks (about 5 μm) within the concrete matrix during service. Additionally, an ASR in pavements is promoted by externally supplied alkalis (de-icing agents). By superposition of both effects the alkali capacity close to the ASR-reactive aggregate aggregate is increased substantially as the externally supplied alkalis can easily penetrate through the microcracks. Thus, both effects intensify the ASR in concrete pavements. Within cooperative research projects the different interdependent influencing factors for a damaging ASR in concrete pavements are studied by experiments as well as by numeric modelling. On the micro-level the ASR-related processes within the aggregate, such as gel-formation or ion-transport, are investigated. On the meso-level, the project focuses on the characterization of degradation effects in the concrete microstructure due to cyclic loading. Further, special attention is paid to the transport behavior of fluids in such pre-damaged concrete structures. A significant increase of the penetration depth of alkaline solutions could not only be observed at different stages of progressing degradation. It becomes also obvious that the ingress of externally supplied alkalis is enhanced by the overrunning traffic. Finally, on the macro-level, the risk of an ASR-damage is assessed.